Modularity as a strategy for medical design - Carla Langella; Salvatore Carleo; Marianna De Luca (Agathón)
In the last decade, collaborations between Design and the biomedical field have become increasingly frequent and effective, thanks to their shared focus on user-centred innovation. Design comes into play when unresolved challenges arise, mainly related to the usability of biomedical products, especially in the field of physical and rehabilitative medicine, where aids used for therapeutic treatments and exercises are often inadequate for scientific advancements and the complex needs of patients and therapists. Through a critical analysis of international best practices, this paper promotes a design approach based on modularity and potential kits for neuro-psychological, orthopaedic, and speech rehabilitation medicine. In this context, the modularity strategy offers an opportunity to develop new design-driven solutions for more flexible, adaptable, ergonomic, comfortable, and sustainable tools.